Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode WASPAS - Septa Fenly Sinaga; Muhammad Syahrizal; Ronda Deli Sianturi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The problem that often occurs is that there is a discrepancy in employee acceptance data in the past by selecting employees with an attitude of not objectivity to recruiting employees. And there are still many employees who do not fit the position with the same knowledge so that when the selection of employees is not appropriate so that they are not driven forward, it will have an impact on other operations. This is certainly not very good because it can affect the smooth operation and inappropriate goals. Therefore we need an Employee Decision Support System so that this method is considered not objective because it is not in accordance with employee data. Based on these problems, it is necessary to build a Decision Support System (DSS) to support the employee recruitment process, by applying the WASPAS method. The application of the WASPAS method will be able to provide the best solution for the company in recruiting employees based on predetermined criteria. The method used in this Decision Support System is the WASPAS method, because it is very suitable for hiring employees on CV. Perfect Core Prime so that in the future because of the WASPAS method it can determine the weight value for each attribute, because it is followed by a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the result of the system based on the specified criteria. So as to produce more accurate employee recruitment and more precise employee targets on the CV. Perfect Core Prime